Building our understanding of social entrepreneurship ecosystems. (4th May 2023) - Lyons, Thomas S.; Roundy, Philip T.
ABSTRACT: While the literature on conventional entrepreneurial ecosystems (EEs) is large and growing, relatively little has been written about social entrepreneurship ecosystems (SEEs). Yet, because social entrepreneurship is distinct from conventional entrepreneurship, it is reasonable to assume that their respective ecosystems differ in significant ways as well. How exactly do they differ, if in fact they do? Do a community's EE and SEE interact, and, if so, in what ways? What system-level attributes make an SEE vibrant? What role do local social entrepreneurship support organizations play in SEEs, and what is their impact on social entrepreneurs and the social and economic fabric of the community? In this thematic issue, we curate a selection of articles that address these and other questions about SEEs and, in so doing, hopefully inspire more research on this important subject while helping to organize it into a cohesive body of research going forward.